Predicting of Long-term Maintenance of Sinus Rhythm after Cardioversion in Patients with Nonvalvular Persistent Atrial Fibrillation - Zharinov O.; Levchuk N.; Ikorkin M.; Sychov O. (Львівський клінічний вісник, 2014)
Introduction. The choice of the optimal strategy for conducting the patients with persistent atrial fibrillation (AF) and the expediency of prolonged antiarrhythmic treatment after cardioversion is highly dependent on the probability of relapse of arrhythmia. The basis of the clinical systematization of paroxysms of AF and one of the most important elements of the algorithm for the management of patients is the criterion of the frequency of episodes of arrhythmia. The processes of fibrosis, electrical perturbation of the atrium and the creation of conditions for circular circulation of the excitation influence a lot on the course and the possibility of the AF persistence. The aim of the study was to determine the role of clinical anamnesis, demographic and a number of indicators of the structural and functional status of the left heart units to predict the conservation of sinus rhythm in patients with persistent AF for 18 months after the cardioversion. Materials and methods. The study included 225 patients (178 men and 47 women), aged 34–79 years, chosen for planned cardioversion. General clinical investigation, ECG, transthoracic and transesophageal echocardiography for detailed evaluation of structure and function of atria and ventricles were performed in all patients. After cardioversion the follow-up investigations were performed every 6 months. In order to restore the sinus rhythm individually, amiodarone, propafenone, etazysin, or their combination with β-blockers, according to the existing recommendations on their application, were used. In 128 cases (56.9 %) an electrical cardioversion was performed to restore the sinus rhythm of the heart. Results. In total, after 18 months the sinus rhythm was maintained in 125 (55.6 %) patients. At the same time, persistent or permanent AF was registered in 100 patients (44.4 %). The age of patients, duration of the disease, heart rate and some left heart structural and functional parameters had independent role for predicting the sinus rhythm maintenance. I.e., left atrium diameter < 45 mm, index of left atrium volume < 50 ml/m2, left ventricular end-diastolic volume < 145 ml, average left atrium appendage ejection velocity ≥ 30 cm/s, absence of spontaneous contrast phenomenon were predictors of the long-term sinus rhythm maintenance. Conclusions. The obtained model is characterized by the high sensitivity, specificity and diagnostic value in the prognosis of maintaining the sinus rhythm of the heart in case of AF.